Development of an Indirect ELISA for the Detection of Newcastle Disease Antibodies with the antigen preparation from the Vero Cell Line - บุตรดี อรวรรณ์; ฉ่ำสิงห์ วิไลรัตน์; เก้าลิ้ม น้องนิด; อุประกรินทร์ นรินทร์ (KKU Science Journal, 2015)
We developed an indirect ELISA test (NDV KP-54) for the detection of antibodies against Newcastle disease virus (NDV) in chickens. The viral antigen was prepared from NDV KP-54 strain which was produced on African green monkey (Vero) cell line and use for an antigen coated plate. Serum samples from 14 flock of chicken (n=219) were tested by the NDV KP-54 ELISA compared with Hemagglutination inhibition test (HI). A cut-off point was established considering the distribution of reactivity values obtained by Two-graph receiver operating characteristic (TGROC) template, The sensitivity and specificity of the ELISA were found to be 79.76% and 88.0% respectively, appropriated that cut-off point of the S/P ratio=0.450. In addition, The developed ELISA kit were evaluated by comparison with the ELISA commercial test kit (BioChek®) on 519 chicken serum The result showed that, the ELISA developed had sensitivity = 86.47% specificity = 84.57% and kappa value at 0.710 indicated that the efficiency of developed ELISA was close to that the commercial test kit and useful for improving NDV disease diagnosis in our laboratory.